2018
DOI: 10.3390/molecules23040798
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Constituents from Roots and Rhizomes of Smilacina japonica

Abstract: Four new steroidal constituents (1–4) along with two known steroidal glycosides (5 and 6) were isolated from the roots and rhizomes of Smilacina japonica. Analysis of their physicochemical properties and spectroscopic profiles identified the compounds as (25S)-5α-spirostan-9(11)-en-3β, 17α-diol (1); (25S)-5α-spirostan-9(11)-en-3β, 12β-diol (2); (25S)-5α-spirostan-9(11)-en-3β, 17α-diol-3-O-β-d-glucopyranoside (3); (25S)-5α-spirostan-9(11)-en-3β, 17α-diol-3-O-β-d-glucopyranosyl-(1→2)-[β-d-glucopyranosyl-(1→3)]-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This inference was confirmed by detailed analysis of the 2D NMR data. The proton and protonated carbon resonances in the NMR spectra of 1 were unambiguously assigned by the HSQC experiments [11,12,13,14]. The 1 H- 1 H COSY correlations of H-4′/H-5′/H-6′/H-7′, along with HMBC correlations (Figure 2) of NH-1′/C-2′, C-3′ and C-7′a, indicate a 1 H -indol-2-one unit in 1 [15]; 1 H- 1 H COSY correlations of H-2″/H-3″/H-4″/H-5″, along with the HMBC correlations of H-2″/C-3″ and C-5″, indicated a pyrrolidine unit in 1 [16]; 1 H- 1 H COSY correlations of H-5/H6/H7/H8, along with the HMBC correlations of H-2/C-3 and C-4, H-5/C-4 and C-8a and the remaining molecular formula C 10 H 5 NO, indicated a 4-quinolinecarboxylic acid unit in 1 [17].…”
Section: Resultsmentioning
confidence: 99%
“…This inference was confirmed by detailed analysis of the 2D NMR data. The proton and protonated carbon resonances in the NMR spectra of 1 were unambiguously assigned by the HSQC experiments [11,12,13,14]. The 1 H- 1 H COSY correlations of H-4′/H-5′/H-6′/H-7′, along with HMBC correlations (Figure 2) of NH-1′/C-2′, C-3′ and C-7′a, indicate a 1 H -indol-2-one unit in 1 [15]; 1 H- 1 H COSY correlations of H-2″/H-3″/H-4″/H-5″, along with the HMBC correlations of H-2″/C-3″ and C-5″, indicated a pyrrolidine unit in 1 [16]; 1 H- 1 H COSY correlations of H-5/H6/H7/H8, along with the HMBC correlations of H-2/C-3 and C-4, H-5/C-4 and C-8a and the remaining molecular formula C 10 H 5 NO, indicated a 4-quinolinecarboxylic acid unit in 1 [17].…”
Section: Resultsmentioning
confidence: 99%
“…The two-dimensional-NMR spectroscopic features confirmed the inference above. The proton and protonated carbon resonances in the NMR spectra of 1 were unambiguously assigned by the HSQC experiments [32,33]. The 1 H- 1 H COSY correlations (Figure 2) of H-2’,6’/H-3’,5’, along with HMBC correlations (Figure 2) of H-2’/C-4’ and H-3’/C-1’, indicated a phenol moiety in 1 [31]; 1 H- 1 H COSY correlations of H-7/H-8, along with the HMBCs of NH-1/C-2, C-8, and C-8a, H-3/C-2, and C-4, and H-5/C-4 and C-7, indicated a 6-hydroxy-2(1 H )-quinolinone moiety in 1 [34]; HMBCs of H-3/C-1’ and H-2’,6’/C-4 confirmed the 6-hydroxy-2(1 H )-quinolinone moiety connected with the phenol moiety via a C-4-C-1’ bond.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to Smilacina atropurpurea , the extract of SJA exhibited similar fungicidal effect, but it had a broader antifungal spectrum. According to previous reports on the constituents of the two plants, there are differences in the chemical structures of saponins isolated from Smilacina atropurpurea and SJA [14, 36–38]. In addition, the report by Ying Zhang et al also suggested that not all saponins had antifungal activity [35].…”
Section: Discussionmentioning
confidence: 99%